Covalent Poly(2‐Isopropenyl‐2‐Oxazoline) Hydrogels with Ultrahigh Mechanical Strength and Toughness through Secondary Terpyridine Metal‐Coordination Crosslinks. (26th September 2019) - Xu, Xiaowen; Jerca, Florica Adriana; Jerca, Valentin Victor; Hoogenboom, Richard
Abstract: The present study reports the synthesis of poly(2‐isopropenyl‐2‐oxazoline) (PiPOx) dual‐crosslinked hydrogels by both covalent and physical (i.e., metal–ligand coordination) interactions. First, chemical crosslinking of a modified PiPOx polymer containing terpyridine (TPy) unit is achieved by reacting with azelaic acid (non‐anedioic acid). Transient crosslinks are subsequently introduced by complexation of the TPy units with different divalent transition metal ions. This strategy provides access to hydrogels with superior mechanical properties compared to the pure covalently crosslinked PiPOx hydrogels. The mechanical properties and water uptake of the hydrogels could be easily controlled by swelling in different aqueous metal ion solutions. PiPOx hydrogels swollen in Zn 2+ solution are found to possess ultrahigh compression strength (9 MPa), remarkable toughness (99 MJ m −3 ) and outstanding self‐recoverability (98% toughness recovery after swelling for 60 min without external stimuli), which are among the highest reported in literature to date. These remarkable properties are assigned to the thermodynamically stable, but kinetically labile Zn 2+ ‐TPy complexes that produce a dynamic network with fewer imperfections and better adaptive properties under mechanical stress compared to those with other metal ions. Abstract : Herein, a new innovative and robust strategy that overcomes the actual challenges for the design and synthesis of hydrogels with ultrahigh toughness is reported. The dual‐crosslinked hydrogels are prepared by covalent crosslinking of a modified poly(2‐isopropenyl‐2‐oxazoline) polymer containing terpyridine units. The hydrogels swollen in Zn 2+ solution show ultrahigh compression strength (9 MPa), remarkable toughness (99 MJ m −3 ) and outstanding self‐recoverability.